Yield Augmentation in Tannia (Xanthosoma sagittifolium (L.). Schott) as Influenced by Tillage, Soil Conditioner and Nutrition - Jayapal, Atul; O., Kumari Swadija (JOURNAL OF ROOT CROPS, 2019)
An investigation was undertaken at College of Agriculture, Vellayani, Kerala to identify ideal tillage system, soil conditioner and nutrition for yield augmentation in tannia during the year 2015-16. The experiment was laid out in split plot design with four replications. The main plot treatments consisted of four tillage systems (l1- conventional tillage with pit system, l2- conventional tillage with mound system, l3- deep tillage with pit system and l4- deep tillage with mound system) and sub plot treatments were two soil conditioners along with a control (s1- control, s2- coir pith @ 500 g plant-1 and s3- rice husk @ 500 g plant-1) and two nutrient management practices (n1- integrated nutrient management (INM) . FYM @ 25 t ha-1 + 80:50:150 kg NPK ha-1 and n2- organic nutrition- FYM @ 37.5 t ha-1 + wood ash @ 2 t ha-1). In the case of INM, half the quantity of FYM and full P were applied as basal dose and remaining FYM and full N and K were applied in three equal splits each at two, four and six months after planting. For organic nutrition, 2/3rd quantity of FYM was given as basal dose and remaining FYM and wood ash were given in three equal splits each at two, four and six months after planting. Dolomite @ 1 t ha-1 was applied uniformily to all plots at land preparation. Results revealed that for yield augmentation in tannia, deep tillage to a depth of 30 cm with pit system of planting, amending the soil with coir pith @ 500g plant-1 and organic nutrition (FYM @ 37.5 t ha-1 + wood ash @ 2 t ha-1) in three splits viz. 2, 4 and 6 MAP along with intercultural operations and earthing up are to be adopted.